TRIBO-CORROSION INVESTIGATION ON MATERIAL 316LX MANUFACTURING RESULT OF 3D PRINTING MATERIAL ADDITIVES IN 5% H2SO4 SOLUTION - Syuryana, Ekha Panji; Komara, Asep Indra; Widyanto, Bambang; Sutarno, Sutarno; Ikaningsih, Manty Aldilani; Aditya, Dicko Adrian; Riskamti, Riskamti; Suardana, Moch Salman Fadillah; Malik, Cagiva Abdul (Jurnal Rekayasa Mesin, 2023)
Tribocorrosion is a type of material degradation caused by simultaneous wear and corrosion of metal surfaces caused by laminar or turbulent flow. Additive manufacturing technology plays an important role in its application to precision components and complex assemblies. This study developed a 316LX material with Fe, Ni, Cr, and other powder alloys that was processed into an ultra-protective wire as a 3D printing filler. This simulation of tribocorrosion conditions was performed on a triboester machine. This simulation is expected to provide important insights and understanding into the behavior and properties of the 316LX 3D printing material, especially when exposed to abrasion and corrosion conditions in a sulfuric acid solution environment. Corrosion Rate Testing of 316LX Material Additives Using Potentiodynamic Methods in a Modified Rotating 5% Sulfuric Acid Fluid. In addition to corrosion rate, the Vickers hardness, metallography, and shrinkage of the 316LX green part material were also tested at 1000oC after sintering.